Strategis Komunikasi Pemimpin Buram (Manajemen Kemandirian Moral) - Dita Destrari Iin Risky Indryani (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2020)
The purpose of writing this article is to find out leaders who have nearsightedness (BURAM). The desired leader today is a leader of humility and true leadership can be imitated and innocent as an example from the life story of Nelson Mandela. A great leader of South Africa, who brought his people from a racist country to a democratic and independent country. Since then many changes in him. So that Nelson Mandela becomes a humble human being and wants to forgive those who have made him suffer for years. The findings can be found that begin to lead from the heart and go out to serve those they lead. Changing character is everything for a true leader. Without change from within, without peace of mind, without humility, without solid integrity, endurance in the face of difficulties and challenges, and clear vision and mission, one can never be a true leader.